Pediatrics, Students, Allied Health and COVID-19 - Carey, Lindsay B. (Journal of religion and health, 2023)
This second issue of JORH for 2023 considers research relating to (1) pediatrics, (2) students, (3) various allied health professions and their related practices, and lastly, (4) COVID-19. An additional reminder is also provided to readers on the call for papers regarding a future issue on "Religion, Spirituality, Suicide, and its Prevention", as well as a new call for papers with respect to "Spiritual Care for People with Parkinson’s Disease and their Caregivers".